A study to assess the effectiveness of nurses led breast feeding Mobile clinic (NLBMC) on breast feeding outcomes in lactating mothers at selected areas of Gurugram - Sonam, Km; Deepak, Deepak; Shalu, Shalu; Banapriya, Banapriya; Yadav, Poonam (Journal of Neonatal Surgery, 2025)
Introduction: Breastfeeding is critical to infant and maternal health, yet many mothers encounter barriers that limit optimal breastfeeding practices, especially in underserved areas. The Nurses-Led Breastfeeding Mobile Clinic (NLBMC) model was developed to deliver accessible, community-based lactation support and counselling. This study aims to assess the effectiveness of NLBMC in enhancing breastfeeding self-efficacy and maternal satisfaction among lactating mothers in selected areas of Gurugram, Haryana. Methods: A quasi-experimental research design was employed with 100 lactating mothers, divided equally into experimental and control groups using systematic random sampling. The experimental group received structured lactation counselling through the NLBMC in addition to conventional care, while the control group received only conventional postnatal support. Data collection tools included a validated breastfeeding self-efficacy scale and a maternal satisfaction level scale. Statistical analysis was conducted using unpaired t-tests. Results: The experimental group exhibited a significantly higher mean breastfeeding self-efficacy score (12.2 ± 1.9) compared to the control group (7.4 ± 1.2), with a mean difference of 4.8 (t=22.3, p=0.0001). Similarly, maternal satisfaction scores were significantly greater in the experimental group (67.1 ± 4.4) than in the control group (37.3 ± 3.9), with a mean difference of 29.8 (t=35.6, p=0.0001). These findings suggest a substantial positive impact of NLBMC services. Discussion: The results indicate that nurse-led mobile breastfeeding support effectively enhances both breastfeeding self-efficacy and maternal satisfaction. These outcomes align with previous studies advocating structured lactation counselling as a strategy to improve breastfeeding practices. The implementation of mobile clinics staffed by trained nurses offers a scalable solution for improving maternal-child health outcomes in resource-constrained settings.